Effectiveness of the MOVE! Multidisciplinary Weight Loss Program for Veterans in Los Angeles - Maria Romanova, MD; Li-Jung Liang, PhD; Max L. Deng; Zhaoping Li, MD, PhD; David Heber, MD, PhD (Preventing Chronic Disease, 2013)
Introduction The purpose of this study was to evaluate the effectiveness of the MOVE! Weight Management Program for Veterans (MOVE!) in achieving weight loss in veterans who attended the multidisciplinary weight management program in the VA Greater Los Angeles Healthcare System. Methods From April 1, 2006, to December 31, 2009, 382 veterans enrolled in the MOVE! program; 377 veterans attended at least 3 group sessions and were included in this study. All veterans were encouraged to complete 8 weekly group sessions on nutrition, lifestyle changes, and behavior modification in a group setting led by a multidisciplinary team. After completing the session, veterans had the option of continuing with a support group that meets monthly. The change in weight from 1 year pre-enrollment in MOVE! to 1, 2, and 3 years postenrollment was analyzed. Results Veterans gained 1.4 kg per year (standard error [SE] = 0.47, P = .003) before enrolling in MOVE!. One year after the enrollment participants lost on average 2.2 kg (SE = 0.42; P < .001). The pre-enrollment slope for weight change was significantly different from the postenrollment slope. Conclusion Findings from this study support the need for a long-term weight management program such as MOVE! in primary care settings to assist overweight and obese VA patients in achieving and maintaining weight loss to reduce the risk and progression of age-related chronic diseases such as diabetes and heart disease.